The Effect of Digital Technology use on Generation Z’S Mountaineering Activities on Mount Andong (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
This study aimed to examine the effect of digital technology use on Generation Z’s mountaineering activities on Mount Andong. The rapid development of digital technology has transformed outdoor recreational sports activities, particularly among Generation Z, who are highly familiar with smartphones, social media, navigation applications, and other digital tools. This study employed a quantitative approach using a descriptive-correlational survey design. The population consisted of Generation Z hikers aged 17–25 years who actively used digital technology during hiking activities. A total of 30 respondents were selected through purposive sampling. Data were collected using a closed-ended Likert-scale questionnaire measuring digital technology use and mountaineering activities. Prior to analysis, the instruments underwent validity and reliability testing. Data analysis techniques included descriptive statistics, Pearson’s product-moment correlation, and simple linear regression using SPSS version 26. The results revealed that the level of digital technology use among Generation Z hikers was categorized as high, with a mean score of 54.67. Similarly, mountaineering activities were also classified as high, with a mean score of 66.77. Pearson’s correlation analysis showed a positive relationship between digital technology use and mountaineering activities (r = 0.359), although the relationship was not statistically significant (p = 0.051). Furthermore, regression analysis indicated that digital technology contributed 12.9% to mountaineering activities, while 87.1% was influenced by other variables outside this study. In conclusion, digital technology functions primarily as a supporting tool rather than the main determinant of Generation Z’s participation in mountaineering activities.